2020
DOI: 10.1055/a-1250-8431
|View full text |Cite
|
Sign up to set email alerts
|

Canaloplasty ab interno (AbiC) – 2-Year-Results of a Novel Minimally Invasive Glaucoma Surgery (MIGS) Technique

Abstract: Purpose The aim of this study is to evaluate the long-term efficacy of a novel minimally invasive glaucoma surgery technique (MIGS), Ab interno Canaloplasty (AbiC). Material and Methods For this retrospective cohort study, we analysed the data of 25 eyes of 23 patients with open angle glaucoma who underwent an AbiC (6 eyes) or in case of an additional cataract, a combined cataract-AbiC procedure (“phacocanaloplasty ab interno”, 19 eyes), respectively. Postoperatively, we investigated the intraocular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
(27 reference statements)
2
11
0
Order By: Relevance
“…The overall reduction in IOP in the entire cohort was 29.0% at 12 months (from 22.5 ± 5.3 mmHg to 15.0 ± 3.6 mmHg). Similar IOP changes have been described for ABeC [ 17 , 18 ] and ABiC [ 21 , 23 , 24 , 25 ] in previous studies. Brusini [ 19 ] reported a more favorable reduction in IOP from 29.4 ± 7.9 preoperatively to 16.8 ± 4.2 mmHg at 12 months probably due to the higher IOP level at baseline compared with the other studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The overall reduction in IOP in the entire cohort was 29.0% at 12 months (from 22.5 ± 5.3 mmHg to 15.0 ± 3.6 mmHg). Similar IOP changes have been described for ABeC [ 17 , 18 ] and ABiC [ 21 , 23 , 24 , 25 ] in previous studies. Brusini [ 19 ] reported a more favorable reduction in IOP from 29.4 ± 7.9 preoperatively to 16.8 ± 4.2 mmHg at 12 months probably due to the higher IOP level at baseline compared with the other studies.…”
Section: Discussionsupporting
confidence: 88%
“…The higher rate of hyphema could be due to the fact that the surgeons used the OMNI system to perform canaloplasty combined with trabeculotomy. The rates of hyphema for the ABiC procedure reported in literature ranges from 0% to 20% [ 21 , 23 , 24 , 25 ]. The higher rate of 20% was found in the study by Kazerounian [ 25 ], which refers to mild hyphema cases with no late sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Patient reliance on medications was also reduced, with the mean number of medications falling from 1.69 at baseline (n=23) to 0.21 at the last follow-up visit (n=11). A 2020 study by Kazerounian et al 20 demonstrated a reduction in mean IOP of 32.5% from 20.24 mmHg ± 5.92 (n = 25) at baseline to 13.67 mmHg ± 2.15 (n = 21, P <0.001) at 24 months following iTrack ab-interno canaloplasty. Medication reduction was also significant, falling from 1.92 ± 1.04 at baseline to 0.05 ± 0.23 at 24 months.…”
Section: Discussionmentioning
confidence: 95%
“…The 24-month results of the present study are in line with previously reported 12-month results. 10 , 19 , 20 A 2018 study by Gallardo et al demonstrated a mean IOP reduction of 32.8% ( P < 0.001) in standalone cases (n = 41) and 31.7% ( P < 0.001) in combined cataract surgery cases (n = 34) respectively, at 12 months. In a 2018 study by Koerber et al, 19 mean IOP reduced from 18.8 ± 5.63 at baseline (n=23) to 14.73 ± 2.97 mmHg at 12 months (n=11).…”
Section: Discussionmentioning
confidence: 98%
“…Clinical evidence indicates that ab-interno canaloplasty is safe and effective in lowering IOP and reducing medication burden in mild-moderate POAG. 22 , 25 , 26 A consecutive case series by Gallardo et al 25 demonstrated the clinical efficacy and safety of iTrack ab-interno canaloplasty over a 12-month period. Overall, 84.9% of eyes experienced a reduction in IOP which was greater than 20%.…”
Section: Discussionmentioning
confidence: 99%